Researching and designing educational games on the basis of “self-regulated learning theory” - Jiang, Feng; Shangguan, Dayan (Frontiers in Psychology, 2022)
As one of the important research fields of educational technology, the potential of educational games has been widely recognized by academic researchers. However, in terms of practical application, it is difficult to balance education and recreation, and problems have also arisen in learners’ cognitive development and skill enhancement. On this basis, this paper initially compares the educational and entertainment aspects of educational games from a learning motivation perspective. It draws on the theory of self-regulated learning and ARCS learning to establish an ARCS learning motivation model and educational game design framework. Finally, it develops a bio evolution education game that is based on this framework, and this verifies that this framework can feasibly guide practice. In drawing on the theory of autonomous learning, this paper discusses the design framework of stimulating and sustaining learning in educational games, and establishes a bridge between user learning behavior and entertainment behavior. This will provide a theoretical and case study reference for the integration of educational purpose and game entertainment into educational games.